Efektivitas Pelaksanaan Praktikum Sistematik Invertebrata Di Laboratorium Biologi Universitas Muhammadiyah Surakarta Ditinjau Dari Nilai Akhir Praktikum - Haq, Ahmad Dliyaul; , Dra. Hariyatmi, M.Si (2016)
Sistematic Invertebrates of practicum is one of the subjects in biology education Muhammadiyah University of Surakarta. This study aims to determine the effectiviy of Invertebrate Systematics practical implementation in terms of the final value. This type of research is evaluative-comparative. This research method is descriptive quantitative by using documentation and interviews techniques. The population of this research is all students of biologi whose follow Systematic Invertebrate of practicum in academic year 2014/2015 and academic year 2015/2016. The sample taked is same as the population. This study uses the effectiveness ratio test to determine how much the level of effectiveness of the practical implementation of Invertebrate Systematics academic year 2014/2015 and academic year 2015/2016. To determine differences in the results of the two samples using a statistical test of Mann-Whitney (non-parametric). The results of that test effectiveness ratio in academic year 2014/2015 is 19.74 and academic year 2015/2016 is 20.34%. Invertebrate Systematics practical implementation is said to be effective if the percentage praktikan that scored ≥ AB more than the practitioner who scored ˂ AB. Mann-Whitney test results, namely 0.639> 0.05, then H0 is accepted meaning there was no significant difference between the practical implementation of Invertebrate Systematics academic year 2014/2015 and academic year 2015/2016. Thus it can be concluded that, deploy Invertebrate Systematics lab in a biology laboratory UMS practical in terms of the final value is not effective (Academic year 2014/2015 and academic year 2015/2016) but there is an increase in the effectivity of academic year 2015/2016